Impact of Agricultural Science Education on Youth Engagement in Agribusiness in Northeast Nigeria - Daniel, Iliya; Yaro, Yusuf (Darul Yasin Al Sys, 2025)
This study investigates the impact of Agricultural Science education on youth engagement in agribusiness in Northeast Nigeria, focusing on its role in fostering entrepreneurial skills, enhancing practical training, and addressing challenges that hinder youth participation in agribusiness ventures. The research employed a questionnaire administered to 704 respondents, including 320 students and 384 youths, to assess the effectiveness of Agricultural Science education in preparing youth for agribusiness. The findings reveal that Agricultural Science education significantly contributes to the development of key entrepreneurial skills, equips students with essential knowledge, and cultivates an entrepreneurial mindset, encouraging youth to pursue agribusiness ventures. Despite these positive outcomes, challenges such as limited access to financial resources, inadequate infrastructure, and insufficient exposure to modern farming technologies impede youth engagement in agribusiness. The study also found that integrating modern agribusiness practices into the curriculum enhances students’ readiness to engage in agribusiness ventures. The study recommends improving hands-on training, incorporating modern agricultural technologies into the curriculum, increasing government support for agripreneurs, and fostering public-private partnerships to address the identified challenges. This research underscores the critical role of Agricultural Science education in promoting youth participation in agribusiness and its potential to contribute to the economic development of Northeast Nigeria.